MENIMBANG SIGNIFIKANSI PERDA SYARIAT ISLAM (Sebuah Tinjauan Perspektif Fikih) - Mth, Asmuni (Islamic University of Indonesia, 2006)
The controversies regarding the emerging of the Shariâah Local Acts ( Perda Syariâah) in several regencies or provinces in Indonesia. The debates about the act appear pros and conts among the societies, government and politicians. Some of them declare that the actcontradict to the Indonesian Constitution and The Indonesian basic ideology Pancasila. Contrary to above perspective is stated that this act can be justified by the constitution. According to the history of Islamic jurisprudence needs to be placed the substance of shariâah or the public interest should be applied over that the textual interpretation of shariâah, for instance tadwin ( codification) and taqnin ( legislation). Kata kunci: perda, syariâah, maslahat, taqnin dan tadwin